Chimeric Antigen Receptor T-Cell Therapies: Barriers and Solutions to Access. Issue 12 (21st December 2022) - Mikhael, Joseph; Fowler, Jessica; Shah, Nina
Abstract : Chimeric antigen receptor T-cell (CAR-T) therapies are relatively new treatments for patients with heavily pretreated hematologic malignancies. Although these innovative therapies can offer substantial benefit to patients with limited alternative treatment options, patient-access barriers exist. Conventional clinical trials are time-consuming and may be limited by strict patient eligibility criteria, resources, and availability of enrollment slots. Because of the complexity of the CAR-T administration process, treatment delivery can be associated with additional burden for the patient, including requiring patients to reside close to treatment centers and remain with a caregiver after infusion. Manufacturing of CAR-T cells is completed in specialized facilities and depends on the availability of reagents, manufacturing workforce, and timely transportation. CAR-T therapy is costly, and many US health plans restrict coverage of cell and gene therapies. Several of the existing challenges because of these barriers have been exacerbated during the COVID-19 pandemic. This review discusses these barriers and proposes some potential solutions to improving patient access, including innovation in clinical trial design and manufacturing, location of treatment delivery, and key stakeholder opinions regarding treatment and reimbursement. We propose a call to action for key stakeholder groups to address these barriers to CAR-T therapy to expand treatment access for patients. Future collaboration between key stakeholders, including payers, regulatory agencies, and industry/academia, will be critical to continue to address these barriers and enhance patient access to these therapies.